Does unconventional monetary policy boost local economic development? The case of TLTROs and Italy - Perdichizzi, Salvatore; Duqi, Andi; Molyneux, Philip; Tamimi, Hussein Al (Journal of Banking & Finance, 2023)
This study investigates the impact of the ECB's Targeted Longer-Term Refinancing Operations (TLTROs) on Italian provinces’ economic development. The program provided preferential funding to banks conditional on them lending to firms. We find that TLTROs did not generate beneficial effects in terms of economic development across Italian provinces. The results show that average firm investment rate fell, driven by small and micro firms, who witnessed a decline in assets. This had a negative, albeit economically small, impact on per capita GDP and unemployment rates at the provincial level. TLTROs were associated with worsened economic conditions for those firms performing well in the pre-TLTRO period. Distressed (zombie) borrowers saw their investment increase, but their post-TLTRO performance did not improve. Overall, TLTROs did not spur economic development through the lending channel across provinces.